Regional campuses and invisible innovation: impacts of non-traditional students in 'Regional Australia'. Issue 6 (3rd June 2022) - Eversole, Robyn
ABSTRACT: This article explores the regional development role of university campuses in less-advantaged peripheral regions with attention to the role of students. In the international literature, regional campuses are theorized as playing three types of regional development roles: developing regional human capital, contributing to regional innovation and supporting regional community development. A case study of regional campuses in the Australian context identifies that current policy framing overlooks the innovative potential of regional campuses and their students. This paper opens an agenda for further research on regional campuses' work with 'non-traditional' student cohorts and its impacts on the development of peripheral regions.